2020
DOI: 10.1063/5.0012247
|View full text |Cite
|
Sign up to set email alerts
|

Flow-induced vibration of inherently nonlinear structures with applications in energy harvesting

Abstract: This paper proposes a novel design for a flow-induced vibration-based energy harvester, consisting of an elastic L-shaped beam, with an inherent nonlinearity in its structural stiffness as an alternative to the classical cantilever beam used in conventional fluidic energy harvester designs. The L-shaped beam supports a prism at its tip and undergoes large-amplitude galloping oscillations. The results from wind tunnel experiments show that by replacing a conventional linear structure that supports the prism wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Moreover, certain customized shapes of a bluff body are studied in an analysis of piezoelectric energy harvesting systems. The paper by Seyed-Aghazadeh et al [ 27 ] investigates the L-shaped beam in which structural stiffness led to nonlinear effects. The proposed design is an alternative to the classical cantilever beam.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, certain customized shapes of a bluff body are studied in an analysis of piezoelectric energy harvesting systems. The paper by Seyed-Aghazadeh et al [ 27 ] investigates the L-shaped beam in which structural stiffness led to nonlinear effects. The proposed design is an alternative to the classical cantilever beam.…”
Section: Introductionmentioning
confidence: 99%
“…The results demonstrated that the proposed structure could adapt to different flow regions. Seyed-Aghazadeh et al [105] studied an FIV-based energy harvester consisting of an inherent nonlinear elastic L-shaped beam. Mcneil and Abdelkefi [17] also derived the nonlinear reduced-order model of an energy harvesting absorber under the effects of mechanical and VIV excitations.…”
Section: Other Applications Of Mechanical Nonlinearitiesmentioning
confidence: 99%
“…Many works have been done to consider the piezoelectric energy harvester when a cubic bluff body is attached to the tip of the beam. The aerodynamic force in this category of works is due to galloping phenomena (Ewere and Wang, 2014;Rezaei and Talebitooti, 2019;Seyed-Aghazadeh et al, 2020;Wang et al, 2020;Zhao et al, 2012Zhao et al, , 2016Zhao et al, , 2019. Unlike VIV that exhibits large amplitudes only when the vortex-shedding frequency is near the structure's natural frequency (lock-in or synchronization), the galloping phenomenon exhibits large amplitudes after a critical speed.…”
Section: Introductionmentioning
confidence: 99%
“…The literature review shows that the main element of piezoelectric energy harvesters are often a cantilever beam with a bluff body in its tip. Therefore, the nonlinear effect due to middle layer stretching effect has been neglected in the previous works (Abdelkefi et al, 2012;Akaydin et al, 2010;Dai et al, 2016;Ewere and Wang, 2014;Gao et al, 2013;Hou et al, 2020Hou et al, , 2022Jia et al, 2018;Li et al, 2022aLi et al, , 2022bLi et al, , 2023Ma et al, 2023;Mehmood et al, 2013;Rezaei and Talebitooti, 2019;Seyed-Aghazadeh et al, 2020;Skop and Griffin, 1973;Sui et al, 2022;Sun et al, 2019;Wang et al, 2020;Yang and He, 2019;Zhang et al, 2022;Zhang and Wang, 2016;Zhao et al, 2012Zhao et al, , 2016Zhao et al, , 2019.…”
Section: Introductionmentioning
confidence: 99%